Counseling on the Implementation of Merdeka Belajar Kampus Merdeka (MBKM) Program at Indragiri Islamic University (UNISI) Tembilahan City, Riau Province - Zulkarnain Zulkarnain; Sri Indarti; Suyanto Suyanto; Reni Suryanita (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
The Merdeka Belajar Kampus Merdeka (MBKM) program, which the Ministry of Education and Culture has launched, a study program is needed that is ready to implement the MBKM program in the curriculum of the study program. For this reason, the MBKM program needs to be disseminated to all state universities and private universities to prepare themselves to implement this government program. Not all universities have the resources to socialize the implementation of MBKM activities in their respective campuses. For this reason, it is necessary to propose Community Service (PKM) activities by the Universitas Riau team for helping the government to socialize the MBKM Program to Private Universities in Riau Province. Especially for universities that are far from the reach of assistance by the central government through the PKM Postgraduate funds of the Universitas Riau. Therefore, this PKM activity chose private partner universities, namely the Indragiri Islamic University (UNISI) in Tembilahan, Indragiri Hilir Regency, Riau Province. The PKM Team conducts MBKM activities in the form of counselling at partner universities in Tembilahan. The activity preparation period to activity reporting is carried out for eight weeks. The target of the resulting activity is the implementation of outreach activities and socialization of the Merdeka Belajar Kampus Merdeka (MBKM) Program at UNISI and the documentation of UNISI's MBKM activities through social media and scientific publications.